#1**+1 **

2log(x) =log(x^2)

-log(y) = The minus sign means that you can divide it by first log(x^2)

-2log(z) =log(z^2), and the minus sign again means you can divide it by the first log(x^2)

So, the whole thing can be written like this:

Log(x^2) / [log(y)*log(z^2)], OR:

**Log [x^2 / yz^2] - Or the first one on your list.**

Guest Mar 4, 2018

#1**+1 **

Best Answer

2log(x) =log(x^2)

-log(y) = The minus sign means that you can divide it by first log(x^2)

-2log(z) =log(z^2), and the minus sign again means you can divide it by the first log(x^2)

So, the whole thing can be written like this:

Log(x^2) / [log(y)*log(z^2)], OR:

**Log [x^2 / yz^2] - Or the first one on your list.**

Guest Mar 4, 2018